SIMETRI DAN GEOMETRI DALAM BATIK TULIS LASEM: SEBUAH PENDEKATAN ETNOMATEMATIKA - Siti Nihlatul Ulya (PT Innovative Academic Journals, 2024)
This research aims to explore the relationship between mathematics and culture through an ethnomathematics approach, focusing on Lasem Hand-Drawn Batik. Lasem Hand-Drawn Batik, as one of Indonesia's cultural heritages, is rich in motifs that are not only artistic but also contain deep mathematical concepts. This research uses a qualitative approach with an ethnographic method, where the researcher analyzes the geometric structure, symmetry, and pattern motifs of Lasem Hand-Drawn Batik to identify the application of mathematical concepts in its production process. The researcher collected data through direct observation of the batik-making process, interviews with batik artisans, and relevant literature studies. The findings show that the motifs of Lasem Hand-Drawn Batik contain various clear mathematical elements, such as symmetry, rotation, and fractals. These concepts not only enrich the aesthetic value of the batik but also provide insights into how culture and mathematics are interconnected in daily life